ACCOUNTING FOR CARBON EMISSIONS UNDER ESG STANDARDS AND ITS REFLECTION ON COST MANAGEMENT FOR ECONOMIC UNITS - Nawfal Hussein Abdullah (Jurnal Ekonomi, Bisnis dan Pendidikan, 2026)
The research aims to explain the knowledge pillars of carbon emission accounting and its role in cost management under ESG standards In view of the development in the business environment, it has become necessary for companies to estimate reports that include information describing the economic unit, as well as identifying and evaluating emission limits, in addition to optional information related to the performance and procedure of reducing carbon emissions, which makes companies either challenging in disclosing carbon emissions within the scope in order to avoid paying the costs of fines as well as adopting responsibility. In order to achieve the goal of the research, the research was applied in the Dijlah Animal Production Company in Baghdad, Iraq, where the indicators of ESG standards were employed and the extent of compatibility of these indicators with the accounting of carbon emissions and the reflection of this on cost management in the economic unit.